Influence of sodium silicate to precursor ratio on mechanical properties and durability of the metakaolin/fly ash alkali-activated sustainable mortar using manufactured sand - Zhang Peng; Wang Cong; Wang Fei; Yuan Peng (Reviews on Advanced Materials Science, 2023)
In recent years, manufactured sand produced from crushed rock has been used as fine aggregate instead of natural sand in construction and industrial fields to minimize the impact of natural sand depletion in nature and society. In this research, the mechanical properties and durability of alkali-activated sustainable mortar using manufactured sand and different sodium silicate (solution) to precursor ratios (SSPR; 0.60, 0.65, 0.70, 0.75, and 0.80) by weight were investigated. Metakaolin and fly ash were used as precursor, sodium silicate (solution) and sodium hydroxide were used as alkali-activator, and manufactured sand made from broken limestone was used to completely replace river sand as fine aggregate to prepare metakaolin/fly ash (MK/FA) alkali-activated sustainable mortar to ensure sustainable development. The compressive, tensile, and flexural strengths, anti-permeability, and crack resistance of MK/FA alkali-activated sustainable mortar were tested. The impact of different SSPRs on the mechanical properties and durability of alkali-activated sustainable mortar was analyzed. Quadratic function fitting models of tensile strength to compressive strength and flexural strength to compressive strength were proposed. Furthermore, the statistical effects of each parameter were explored using analysis of variance and F-test of statistical analysis. The experimental results indicate that the SSPR has a remarkable effect on the mechanical properties and durability of MK/FA alkali-activated sustainable mortar. When the SSPR is in the range of 0.6–0.8, the compressive, tensile, and flexural strength of the alkali-activated sustainable mortar initially increased and then decreased; however, there is an opposite trend in water penetration depth and crack index. MK/FA alkali-activated sustainable mortar exhibits best compressive strength, tensile strength, flexural strength, anti-permeability, and cracking resistance of 40.2 MPa, 3.38 MPa, 4.3 MPa, 41.3 mm, and 245 mm, respectively, at SSPR of 0.7. The experimental findings of this study can provide theoretical guidance for practical engineering of alkali-activated sustainable mortars using manufactured sand.